1982
DOI: 10.1111/j.1471-0528.1982.tb03661.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of preclinical carcinoma of cervix in a British population

Abstract: Summary. Quantitative knowledge of the natural history of cancer of the cervix is essential to the design of optimal screening programmes. We have estimated the incidence and prevalence of cervical intraepithelial neoplasia in a population of women receiving cytological examinations, and compared the results with those from other series. Relative risk of disease is reported in relation to easily identified variables (marital status, parity, contraceptive use, symptoms) which are likely to be of practical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
9
2
1
Order By: Relevance
“…The estimates of probabilities and transition times for sequential progression from one stage to the next have varied widely, however, and the resulting vague idea about the true incidence and untreated progression of in situ lesions has severely hampered a rational and cost-effective design of population-based screening measures (Kessler, 1974;Knox, 1982;Hakama et al, 1985). The incidence of cancer in situ has been calculated in only few studies (Dunn & Martin, 1%7, Bibbo et al, 1971;Albert, 1981;Boyes et al, 1982;Parkin et al, 1982). Parkin et al (1982) derived the incidence rate of cancer in situ from the prevalence figures obtained at a second investigation after a cytologically normal smear.…”
Section: Resultsmentioning
confidence: 99%
“…The estimates of probabilities and transition times for sequential progression from one stage to the next have varied widely, however, and the resulting vague idea about the true incidence and untreated progression of in situ lesions has severely hampered a rational and cost-effective design of population-based screening measures (Kessler, 1974;Knox, 1982;Hakama et al, 1985). The incidence of cancer in situ has been calculated in only few studies (Dunn & Martin, 1%7, Bibbo et al, 1971;Albert, 1981;Boyes et al, 1982;Parkin et al, 1982). Parkin et al (1982) derived the incidence rate of cancer in situ from the prevalence figures obtained at a second investigation after a cytologically normal smear.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of the age-specific prevalence of dysplasia, carcinoma in situ (c.i.s.) and preclinical invasive disease in unscreened populations are available from several studies (Dunn & Martin, 1967;Bibbo et al, 1971;Fidler et al, 1968;Sweetnam et al, 1981;Parkin et al, 1982b). Prevalence of clinical cancer (women currently alive who have had a previous diagnosis of clinical cancer) must be estimated from incidence of clinical cancer prescreening, and survival rates for the same time period.…”
Section: Simulation Of Demographic Eventsmentioning
confidence: 99%
“…There has been a recent trend to the use of the terminology "cervical intra-epithelial neoplasia" (C.I.N.) for all pre-invasive abnormalities of the cervix (Richart & Barron, 1969;Koss, 1978 (Rotkin, 1973) or their partner (Skegg et al, 1982) The incidence of dysplasia (transfer 1 to 2) is derived from observed data (Dunn & Martin, 1967;Parkin et al, 1982b), and transition from clinical cancer to death (5 to 8) is derived from age/duration-specific survival rates for England and Wales (OPCS, 1980). Dysplasia is a relatively transient condition, and the high regression rates (2 to 1) used here (12.5-25% per year) are consistent with observed data (Stern & Neely, 1964;Fox, 1967;Nasiell et al, 1976).…”
Section: Simulation Of the Disease Processmentioning
confidence: 99%
See 2 more Smart Citations